2018
DOI: 10.1111/1751-2980.12672
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgicel® (Fibrillar) for preventing bleeding after endoscopic submucosal dissection for gastric epithelial tumors

Abstract: Objective Surgicel (Fibrillar), i.e. oxidized regenerated cellulose, is used to control oozing bleeding after surgery, but few studies have assessed its effect on complications after endoscopic treatment. The aim of this study was to evaluate the efficacy of Surgicel for preventing bleeding after endoscopic submucosal dissection (ESD) for gastric epithelial tumors. Methods From November 2012 to December 2013 patients scheduled for ESD of gastric epithelial tumors were prospectively enrolled in this study. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Surgicel (Fibrillar) (Johnson & Johnson, PlazaNew Brunswick, NJ, USA), an oxidized regenerated cellulose, and histamine 2 receptor antagonists (H 2 RA) can decrease the incidence of hemorrhage in the same way as PPIs. For patients at a high risk of hemorrhage, adding Surgicel to H 2 RA can be considered . For the closure of the artificial ulcer, the traditional clipping is technically difficult when the mucosal defect is large.…”
Section: Precautions Against Bleeding After Gastric Esdmentioning
confidence: 99%
“…Surgicel (Fibrillar) (Johnson & Johnson, PlazaNew Brunswick, NJ, USA), an oxidized regenerated cellulose, and histamine 2 receptor antagonists (H 2 RA) can decrease the incidence of hemorrhage in the same way as PPIs. For patients at a high risk of hemorrhage, adding Surgicel to H 2 RA can be considered . For the closure of the artificial ulcer, the traditional clipping is technically difficult when the mucosal defect is large.…”
Section: Precautions Against Bleeding After Gastric Esdmentioning
confidence: 99%
“…Grey diamond: Pooled estimate of effect size. Its width corresponds to its 95% CI [19,52,53,[55][56][57].…”
Section: Pairwise Meta-analysis Resultsmentioning
confidence: 99%
“…Of the total, 54 proved potentially relevant for full-text review. Of these, 31 articles on the management of ESD-induced ulcers via endoscopic closure (hemoclips, endoclips, endoloop + endoclips, detachable snare + clips, OTSC + through-the-scope clips [TTSC], overstitch suturing, handsewn suturing) [31][32][33][34][35][36][37][38][39][40][41][42], tissue shielding methods (PGA sheets-based) [10,[43][44][45][46][47][48][49], and hemostatic powder/gel spray [18,19,[50][51][52][53][54][55][56][57][58], matched the selection criteria and were included in the systematic review. The key characteristics of each included study appear in Table 1.…”
Section: Identified Studies and Qualitymentioning
confidence: 99%
“…Researchers showed that large mucosal defects (> 21 mm in diameter) were more likely to bleed, which indicates that the risk of bleeding associated with ESD is signi cantly higher than that associated with EMR [26]. Usually, most post-ER bleeding episodes are successfully managed using endoscopic intervention; however, delayed diagnosis and treatment may be fatal in some cases [27]. Perforation may also be associated with fatal outcomes; intra-abdominal leakage of intestinal contents can cause secondary and serious complications such as peritonitis [28].…”
Section: Discussionmentioning
confidence: 99%